The Role of Parents in School Management in Private and Government Secondary Schools in Adama Town - Alemu Disassa Mulleta; Wosene Alemu Demissie; Zebene Gelagile (Ethiopian Journal of Science and Sustainable Development, 2020)
TThe major purpose of this study was to investigate the status of parental involvement in school management. To this end, a descriptive survey research design has been used to collect relevant data from 35 representatives of parents and 40 directors/vice directors in five government and seven private secondary schools in Adama City Administration using questionnaire, focus group discussion, and key informant interview. The quantitative data were analyzed using descriptive and inferential statistics while the qualitative data were analyzed thematically. Results of the study reveal that both parents and directors seem to have positive attitude towards parental involvement in school management, yet the actual practice on the ground is not satisfactory. Parents’ involvement is limited to raising and supervising the utilization of school fund and fulfilling school infrastructure. They have minimal involvement in planning school activities, supervising teachers, providing of pedagogical support, and recruiting students due to barriers such as time constraint, lack of initiative, lack of awareness on how to contribute, and absence of incentives for parents. Although there are some differences in their mean values, statistically significant differences between private school and government school parents with regards to their involvement in school management were observed only on two domains: raising fund and managing students’ discipline. Hence, working closely with community based association, raising parents’ awareness through trainings, and providing incentives have been recommended.